PENYUSUNAN NILAI TUKAR PETANI (NTP) PADA TANAMAN PANGAN DAN PERKEBUNAN DI KABUPATEN KONAWE SELATAN - Salahuddin, Salahuddin; Limi, Muhammad Aswar; Zani, Munirwan; Abdullah, Sukmawati (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
South Konawe Regency, as an agricultural region with a large population and a dominant proportion of households working in agriculture, pays attention to farmers' welfare as very strategic. One of the tools to measure farmer welfare currently used is the Farmer Exchange Rate (NTP). The aim of carrying out this research activity is to determine the farmer's exchange rate (NTP), and the factors that influence the farmer's exchange rate food crop and plantation sectors in South Konawe Regency. This research uses a quantitative research approach. The sample for this study was determined to be 600 farmers, consisting of 300 food crop farmers (150 lowland rice farmers, 85 corn farmers, and 65 cassava farmers) and 300 plantation crop farmers (105 cocoa farmers, 65 cashew farmers, 65 pepper farmers, and 65 coconut farmers). The sampling technique that will be used is multistage random sampling. To collect research data, use the observation method, questionnaire method, and documentary method. Data were analyzed using descriptive analysis, NTP analysis and multiple linear regression analysis. The research results showed that the Farmer Exchange Rate (NTP) in the food crop and plantation sectors in 2021 was 97.21% and 97.21% (NTP < 100), meaning that food crop and plantation farmers experienced a deficit. Production prices rose less than increases in consumption prices and production costs. The level of farmer welfare has decreased compared to the previous level of farmer welfare. The factors or variables of land area and farmer expenditure significantly influence the NTP of farmers in the field of food crops by 93%. The farmer's land area variable has a significant positive effect on NTP, while farmer expenditure has a significant negative effect on NTP in the field of food crops. Factors or variables of family responsibilities, income and farmer expenses significantly influence the NTP for plantation crops at 96%. Farmers' income has a significant positive effect on NTP, while family responsibilities and farmers' expenses have a significant negative effect on NTP in plantation crops in South Konawe Regency.